JARINGAN KEKERABATAN MATRILINEAL SEBAGAI MODAL SOSIAL PEREMPUAN CALEG DALAM PEMILU 2014 - Indah Adi Putri (Universitas Andalas, 2017)
This paper discusses the matrilineal kinship network used as social capital by women legislative candidate in the 2014 election. It is known that in Minangkabau which adheres to matrilineal kinship system, where there are ninik mamak and bundo kanduang that play a big role in the people. This is a social capital that can be used by women candidates as a strategy to get and gain voice support. The research was conducted on three women candidates who advanced for DPRD West Sumatra, two of them are petahana. The research method is qualitative with case study type. Data were collected by conducting in-depth interviews to women legislative candidates, and those involved in the process of winning candidates, such as ninik mamak and bundo kanduang.